Corona Virus (COVID-19) Pandemic Knowledge, Perceptions and Practices among Nigerian Academic Communities - Aliyu Olugbenga Yusuf; Mazeedat Adeola Olajide-Yusuf; Muili Folaranmi Olajide (Goodwood Publishing, 2022)
Purpose: This study assesses Nigerian academic communities’ (NAC) knowledge, perception, and practices regarding the COVID-19 pandemic. Research Methodology: Online snowball sampling technique with 5-point Likert scale online questionnaire was used to assess NAC knowledge, perception, and practices amidst coronavirus pandemic. About 368 participants comprised of academic and non-academic staff from north central geopolitical zone of Nigeria participated in the study. Responses were analysed using the SPSS. Result: NAC gathered, shared, and updated their knowledge about COVID-19 mostly through social media. Participants professed social media as the most effective platform for education and updates on COVID-19 compared to the conventional media and government sources. Despite that, participants were discovered to have slight issues in differentiating real news from fake ones. The participants reasonably practised precautionary measures as directed by the government and centre for disease control. Limitations: This study is limited to academic environment while COVID-19 affects all sundries and sectors of the economy respectively. Contribution: This study contributes to the knowledge and insight of COVID-19 among NAC and suggests means of managing the virus to avoid further spread.